Effectiveness of dose-escalated topiramate monotherapy and add-on therapy in neurosurgery-related epilepsy: A prospective study. Issue 52 (24th December 2020) - Liu, Yu-Tse; Chen, Guo-Tai; Huang, Yin-Cheng; Ho, Jih-Tsun; Lee, Cheng-Chi; Chang, Chen-Nen
Abstract: Background: Lesional and symptomatic causes of epilepsy are the most common neurological disorders of the brain. Topiramate effectively controls newly diagnosed epilepsy and refractory focal seizures, but high-dose topiramate does not improve seizure control. This study aimed to evaluate the clinical efficacy and safety of dose-escalated topiramate as first-line monotherapy and add-on therapy in patients with neurosurgery-related epilepsy. Material and Methods: A total of 55 neurosurgical patients with epilepsy were divided into monotherapy and add-on therapy groups and both groups received topiramate via the dose-escalation method. The primary efficacy outcomes were seizure-free rate and seizure response rate. Adverse events and seizure frequency were recorded. Results: The seizure response rate in the first month of monotherapy was significantly better than that of add-on therapy (89% vs 65%, P  < .05), but no significant differences were found in seizure response rates between the 2 groups after 2 months of treatment. Both monotherapy and add-on therapy were effective in controlling seizures, with mean seizure frequency of 0.725 vs 0.536 and seizure-free rate of 88% vs 78.6%. Both treatments showed good improvement of seizure frequency in patients without tumor. The efficacy of monotherapy was better than that of add-on therapy (80% vs 29.2%) in patients with body mass index (BMI) ⩽24. However, add-on therapy was better than monotherapy (76.7% vs 21.4%) in patients with BMI > 24. Dizziness (25.5%) and headache (16.4%) were the most common adverse events. No severe adverse event such as cognitive impairment was observed. Conclusions: Dose-escalated topiramate monotherapy and add-on therapy demonstrate good efficacy and safety, with fewer adverse events in seizure control in neurosurgical patients.